Desmoid Tumours—A Review - S. Bhattacharya; B. K. Acharya; M. S. D. Jaiswal; D. C. Srivastava; A. Chaturvedi; N. C. Misra; R. P. Sahi (Indian Journal of Plastic Surgery)
Seventeen cases of Desmoid tumours, 7 abdominal and 10 extraabdominal were chosen for this study and managed in the last five years. A wide local excision and one stage reconstruction was attempted in them. Simple reconstructive mesures viz. primary closure aided by internal fasciotomies and split skin grafting were found adequate for extra abdominal sites whereas abdominal desmoids after ablation usually left a defect requiring prolene mesh and local skin flaps.